Export versus FDI in Cournot duopoly framework - Andrzej Cieslik (Institute of Economic Research (IER), 2015)
In this paper we study the choice between exporting and foreign direct investment (FDI) in the Cournot duopoly framework. First, we identify the conditions necessary for exporting and FDI, depending on costs of exporting and the cost of foreign investment. Then, we discuss various proximity-concentration tradeoffs. Finally, we demonstrate that six possible types of equilibriums may emerge depending on various combinations of the key parameters of the model. These equilibriums include: a monopoly FDI equilibrium, a monopoly exporting equilibrium, a domestic monopoly equilibrium, a duopoly FDI equilibrium, a duopoly exporting equilibrium, and no entry equilibrium.
Keywords: F23; 330; exporting; foreign direct investment; proximity-concentration tradeoff